2014
DOI: 10.1093/europace/eut415
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of echocardiographic parameters associated with left ventricular diastolic dysfunction on short- and long-term outcomes of catheter ablation of atrial fibrillation

Abstract: Early results of the catheter ablation, but not the late rhythm outcome, are influenced by an impaired mitral inflow pattern, which is associated with LVDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
2
21
1
Order By: Relevance
“…However, late recurrences are common and associated with more advanced atrial substrate associated with structural heart disease. [436][437][438][439][440][441][442][443][444][445][446] It is in this context that it is important to consider the various types of underlying atrial cardiomyopathy and how they may affect ablation outcomes. This is timely, as it has recently been observed that lone AF is a rapidly disappearing entity as we recognize conditions such as sleep apnoea, obesity, endurance exercise etc.…”
Section: Ablation Of Atrial Tachyarrhythmiamentioning
confidence: 99%
“…However, late recurrences are common and associated with more advanced atrial substrate associated with structural heart disease. [436][437][438][439][440][441][442][443][444][445][446] It is in this context that it is important to consider the various types of underlying atrial cardiomyopathy and how they may affect ablation outcomes. This is timely, as it has recently been observed that lone AF is a rapidly disappearing entity as we recognize conditions such as sleep apnoea, obesity, endurance exercise etc.…”
Section: Ablation Of Atrial Tachyarrhythmiamentioning
confidence: 99%
“…Kosiuk et al [27] showed that E/A mitral inflow pattern (early to late mitral inflow velocity ratio, assessed by pulsed-wave Doppler at the level of the mitral valve), which is associated with LV diastolic dysfunction, was the best pre-procedural predictor of short-term AF recurrence during the first week after PVI. An E/A ratio of 1.35 was the cut-off value with the highest sensitivity and specificity for predicting early AF recurrence.…”
Section: Left Ventricular Diastolic Dysfunctionmentioning
confidence: 99%
“…This discrepancy may be due to different definitions of LV diastolic dysfunction applied in both studies. Moreover, Kosiuk et al [27] analyzed the results of CA after only a single procedure, and it can also explain the contradictory results because, as mentioned above, late AF recurrences are mainly due to pulmonary vein reconnections [28,29]. Finally, a limited number of patients with severe LV diastolic dysfunction might preclude evaluation of other parameters, like E/e' ratio as predictors of both, short-and longterm AF recurrences after CA.…”
Section: Left Ventricular Diastolic Dysfunctionmentioning
confidence: 99%
“…However, late recurrences are common and associated with more advanced atrial substrate associated with structural heart disease. 436446 …”
Section: Imaging Techniques To Detect Atrial Cardiomyopathies Mappingmentioning
confidence: 99%